Some Experience from the Analysis of Existing 40 Years Old Prestressed Bridges in the North of Slovakia - Martin Moravcik; Peter Kotes; Miroslav Brodnan; Patrik Kotula (Communications - Scientific letters of the University of Zilina, 2014)
The paper deals with the analysis of the chosen short-span bridges from precast prestressed concrete girders. The analysis has been performed at the Department of Structures and Bridges recently. Part of the current technical condition assessment of these structures comprised the load carrying capacity and remaining life time determined by calculation [1, 2 and 3]. The load carrying capacity was calculated in compliance with the previous Slovak standards and new European standards.